CSR Books. - UTS ePress (Broadway, NSW : UTS ePress, 2014)
"CSR Books is an imprint of Cultural Studies Review"--CSR Books, no. 1 title page.
Title from Book 1 PDF title page (viewed on 15 June 2015)
Mode of access: Available online. Address as at 15/06/15
Selected for archiving
Keywords: Culture -- Australia; Australian